The Employee Perspective on Pay Transparency - Tenhiälä, Aino; Karaeminogullari, Aysegul; Varma, Arup (Journal of Total Rewards, 2023)
This study asked a random sample of employees about their perceptions of pay transparency with regard to pay processes, guidelines and methods employers use to communicate pay information. The results affirm that employee perceptions of pay transparency and a culture of pay secrecy differ substantially across employees from various organizational contexts. Employers should anticipate that there will be increasing demands from governments and employees for pay transparency. Given the positive outcomes commonly associated with pay transparency, it benefits employers to be more open with their rationale for employee pay practices. However, employers must be aware of the challenges associated with pay transparency, which include having sound pay systems based on clear policies and rationale, and providing individual pay privacy. Employers are advised to make sure that managers understand the pay system and pay transparency policies, so they can accurately communicate pay programs.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas ::5311.04 Organización de recursos humanos; ODS 8 - Trabajo decente y crecimiento económico; ODS 10 - Reducción de las desigualdades; ODS 16 - Paz, justicia e instituciones sólidas